Factors affecting body composition in preterm infants: Assessment techniques and nutritional interventions - K. Strydom; E. Van Niekerk; M.A. Dhansay (Elsevier, 2019)
Limited research has been conducted that elucidates the growth and body composition of preterm infants. It is known that these infants do not necessarily achieve extra-utero growth rates and body composition similar to those of their term counterparts. Preterm infants, who have difficulty in achieving these growth rates, could suffer from growth failure. These infants display an increased intra-abdominal adiposity and abnormal body composition when they achieve catch-up growth. These factors affect the quality of weight gain, as these infants are not only shorter and lighter than term infants, they also have more fat mass (FM) and less fat-free mass (FFM), resulting in a higher total fat percentage. This could cause metabolic syndrome and cardiovascular problems to develop later in a preterm infant's life. The methods used to determine body composition in preterm infants should be simple, quick, non-invasive and inexpensive. Available literature was reviewed and the Dauncey anthropometric model, which includes skinfold thickness at two primary sites and nine body dimensions, is considered in this review the best method to accurately determine body composition in preterm infants, especially in resource-poor countries. It is imperative to accurately assess the quality of growth and body composition of this fragile population in order to determine whether currently prescribed nutritional interventions are beneficial to the overall nutritional status and quality of life-in the short- and long-term-of the preterm infant, and to enable timely implementation of appropriate interventions, if required. Key Words: body composition, developing country, nutritional interventions, preterm infant, skinfold thickness